1999
DOI: 10.1002/(sici)1099-0992(199912)29:8<1049::aid-ejsp985>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

About the impact of automaticity in the minimal group paradigm: evidence from affective priming tasks

Abstract: Two experiments examined whether novel, minimal ingroups are automatically associated with positive aect while outgroups do not elicit such positive evaluative default. Participants were assigned to social categories in a typical minimal group setting and subsequently administered a masked priming task, i.e. prime words were not consciously recognized. Following either the presentation of a priori positive or negative words or the presentation of the group labels, participants classi®ed adjectives with regard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
136
3
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(153 citation statements)
references
References 53 publications
12
136
3
2
Order By: Relevance
“…This finding speaks to questions raised about the cause of an implicit in-group bias (Otten & Wentura, 1999). That is, not only did we observe evidence that the self is used as an anchor in implicit judgments about one's group, but we showed as well that this process is limited by the motivational pressures affecting the self.…”
Section: Discussionsupporting
confidence: 75%
“…This finding speaks to questions raised about the cause of an implicit in-group bias (Otten & Wentura, 1999). That is, not only did we observe evidence that the self is used as an anchor in implicit judgments about one's group, but we showed as well that this process is limited by the motivational pressures affecting the self.…”
Section: Discussionsupporting
confidence: 75%
“…As with research on EC, such effects were originally demonstrated for explicit attitudes. Recent research found similar effects for implicit attitudes (e.g., Ashburn-Nardo et al, 2001;Castelli et al, 2004;DeSteno et al, 2004;Otten & Wentura, 1999;Pratto & Shih, 2000). Even though there is no evidence for a particular pattern of mediation available yet, the APE model implies that minimal group situations may change associative evaluations of the in-group, which then provide a basis for evaluative judgments about the in-group.…”
Section: Interplay Of Explicit and Implicit Attitude Changementioning
confidence: 98%
“…More precisely, such "implicit" measures allow one to infer evaluations from response latencies or error rates, typically in speeded categorization Based on evidence that automatic evaluations assessed by these measures reliably predict judgments and behavior (for a review, see , researchers became increasingly interested in questions pertaining to their origin and change (Gawronski & Bodenhausen, 2006;Petty, Briñol, & DeMarree, 2007;Rudman, 2004;Wilson, Lindsey, & Schooler, 2000). For instance, with regard to their origin, researchers have explored the roles of evaluative conditioning (e.g., Olson, & Fazio, 2001), cognitive balance (e.g., Gawronski, Walther & Blank, 2005a), and ingroup favoritism (e.g., Otten & Wentura, 1999). Moreover, research addressing change in automatic evaluations has investigated various mechanisms, including cognitive dissonance (e.g., Gawronski & Strack, 2004), attitude-related education programs (e.g., Rudman, Ashmore, & Gary, 2001), and extended training in negating evaluative responses (e.g., Gawronski, Deutsch, Mbirkou, Seibt, & Strack, 2008a;Kawakami, Dovidio, Moll, & Hermsen, 2000).…”
Section: Function Of Task Characteristics Of the Measurementioning
confidence: 99%